Developmental interneuron subtype deficits after targeted loss of Arx. Issue 1 (December 2016) - Marsh, Eric; Nasrallah, MacLean; Walsh, Caroline; Murray, Kaitlin; Nicole Sunnen, C.; McCoy, Almedia; Golden, Jeffrey
Abstract Background Aristaless-related homeobox (ARX ) is a paired-like homeodomain transcription factor that functions primarily as a transcriptional repressor and has been implicated in neocortical interneuron specification and migration. Given the role interneurons appear to play in numerous human conditions including those associated withARX mutations, it is essential to understand the consequences of mutations in this gene on neocortical interneurons. Previous studies have examined the effect of germline loss ofArx, or targeted mutations inArx, on interneuron development. We now present the effect of conditional loss of Arx on interneuron development. Results To further elucidate the role ofArx in forebrain development we performed a series of anatomical and developmental studies to determine the effect of conditional loss ofArx specifically from developing interneurons in the neocortex and hippocampus. Analysis and cell counts were performed from mouse brains using immunohistochemical and in situ hybridization assays at 4 times points across development. Our data indicate that early in development, instead of a loss of ventral precursors, there is a shift of these precursors to more ventral locations, a deficit that persists in the adult nervous system. The result of this developmental shift is a reduced number of interneurons (all subtypes) at early postnatal and later time periods. In addition, we find that X inactivation is stochastic, and occurs at the level of the neural progenitors. Conclusion These data provide further support that the role ofArx in interneuron development is to direct appropriate migration of ventral neuronal precursors into the dorsal cortex and that the loss ofArx results in a failure of interneurons to reach the cortex and thus a deficiency in interneurons.